A Novel Design for a Robot Grappling Hook for use in a Nuclear Cave Environment. Issue 21 (2016) - Bridgwater, Tom; Griffiths, Gareth; Winfield, Alan; Pipe, Tony
Abstract: Within the field of robotics there exist few designs for detachable grappling hooks. This paper focusses on the novel design of a detachable grappling hook for use within a nuclear cave environment. The design seeks to exploit the complex network of pipes that is present within a nuclear cave. It is hoped that the grapple may be used to aid with mapping and characterisation of the nuclear cave, as well as increasing the movement capabilities of robots within the cave. It is shown that our prototype grapple is able to support on average 2.4kg of mass, or thirty times its own weight. In addition when dropped from a height of 7.5cm, which removes ballistic instability, the grapple is able to engage itself 87% of the time. Finally the minimum speed that the grapple must be travelling, in order to secure itself to its target, is found to be 1.08m/s.